An ANDROID based gesture control robot. Issue 4 (4th July 2017) - Jain, Monika; Tiwari, Usha
Abstract: To reduce the programming burden of various robots, now a days Gesture based programming is a new form of representation. It will result in more innovative programming for complex real word problem based on non -verbal communication. Most of the past work had mainly focused on areas like navigation and manipulation; only some of the robotic systems are equipped with exile user interfaces that permit controlling the robot by natural means. To capture gestures through an android Smartphone this paper analyses the motion technology with an inbuilt accelerator and a Bluetooth module which controls the kinetics of a prototype robot. An application has been developed on the android OS to synchronize the Smartphone's gestures with the robot. The android OS platform is gaining popularity among software developers due to its powerful capabilities and open architecture. This paper also highlights the application of such a prototype robot in various fields like domestic, defence and disaster management.